IMPLEMENTASI KEKUATAN MENGIKAT PADA PERJANJIAN HUTANG PIUTANG SECARA LISAN/DIBAWAH TANGAN DI TINJAU BERDASARKAN PASAL 1338 KUHPERDATA - Aris Setyanto Pramono; Safiulloh Safiulloh (Res Justitia : Jurnal Ilmu Hukum, 2023)
Accounts Payable Accounts payable is part of the socio-economic activities that usually occur in the community based on the need to meet household needs or business (business) capital. The person who borrows is called the debtor, who gives the loan is called the creditor. The problem is if the debt cannot be paid according to the agreement/agreement because the debtor is experiencing financial difficulties (financial). So the debtor who cannot pay is called a breach of promise (default) so that it can be billed and even sued. In religion, debts and debts are not an easy matter because they are obligations that must be fulfilled both by themselves and by their heirs because they can be brought to death. In general, a diwali debt transaction with an oral or written agreement/agreement is an agreement that contains the rights and obligations of both parties, and serves as evidence of settlement at a later date. In principle, every agreement must be carried out in good faith. And the agreement made by both parties applies as law for those who make it (the principle of pacta shun servanda). This article analyzes how a debt agreement was born orally or privately. Whether the agreement is legally declared valid and becomes binding law for those who make the agreement. With the debt agreement, which is only carried out verbally, if at any time one of the parties does not carry out its obligations "achievement" or is deemed to have failed to carry out its obligations "default" can be declared guilty and on the basis of any evidence when the debt-receivable agreement is carried out verbally only, so whether the agreement has the executive power to be able to take assets from one of the parties who are declared 'defaults' as a form of compensation for both the debtor (who borrows) and the creditor (who provides the loan).